2/6x-19=3/2x-11

   26x - 19 = 32x - 1136x - 19 = 22x - 1118x - 57 = 4x - 2218x - 4x = -22 + 5714x = 35x = 3514x = 52

  • 5
Solution

1

Simplify 2/6x to 1/3x

1/3x−19=3/2x−11


2

Multiply both sides by the common denominator 6x

2−114x=9−66x


3

Subtract 2 from both sides

−114x=9−66x−2


4

Simplify 9−66x−2 to −66x+7

−114x=−66x+7


5

Add 66x to both sides

−114x+66x=7


6

Simplify −114x+66x to −48x

−48x=7


7

Divide both sides by −48

x=7/−48


8

Simplify 7/−48 to −7/48

x=−7/48
  • -1
What are you looking for?